ARISTOTLE AND THE ACCENTS THE CATEGORIES OF SPEECH IN JEWISH AND OTHER AUTHORS - Revell, E. J. (Journal of Semitic studies, 1974)
E. J. REVELL; ARISTOTLE AND THE ACCENTS THE CATEGORIES OF SPEECH IN JEWISH AND OTHER AUTHORS, Journal of Semitic Studies, Volume XIX, Issue 1, 1 March 1974, Pag